Pengaruh Kepemimpinan dan Rasa Kebersamaan terhadap Kinerja Pegawai: Keterlibatan Karyawan sebagai Mediasi - Mauludin, Hanif; Liana, Yuyuk; Kurnia, Neni (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
This study analyzes the influence of leadership and a sense of community on employee performance, with employee engagement as a mediator at the Malang Regency Tourism and Culture Office. SEM-PLS was used as the analysis tool, with 42 civil servants selected as respondents through purposive sampling. The results showed that leadership had a positive but insignificant effect on employee performance. However, leadership and a sense of community both had a positive and significant effect on employee engagement. Importantly, a sense of community also had a direct positive and significant effect on employee performance, indicating that a strong sense of community can improve performance. Furthermore, employee engagement was shown to have a positive and significant effect on employee performance. Therefore, strengthening togetherness within an organization is an effective strategy to improve employee engagement and performance.